An Analysis of Motivational Actions Used by the Lecturers in Teaching Reading to Motivate the Students of Syariah Faculty at IAIN STS Jambi - Yenti Yenti (Universitas Batanghari Jambi, 2019)
This article was written to know motivational actions used by the lecturers in teaching reading English at Syariah Faculty at IAIN STS Jambi. This research was done to the first year students. The design of this research was descriptive research by using observation technique and written interview. Source of the data was all the activities of the English lecturers in the classroom. The result shown that all the English lecturers only applied six of the seven kinds of motivational actions. Those are: using visual aids, giving a praise, giving chance to the students to read, building a fun situation, giving direct rewards, and giving positive example. And building students’ knowledge was not applied by all of the English lecturers. From the research, it can be explained that all students were motivated in studying reading English when the lecturers applied motivational actions in teaching reading.